Analisis Kelengkapan Pengisian Berkas Rekam Medis Rawat Inap Di RS X di Kabupaten Klaten - Syahputri, Rezyana Budi; Haryanti, Rheni; Rohma, Freshtasya Nora Putri (Jurnal Manajemen Informasi dan Administrasi Kesehatan, 2024)
One of the essential support services in hospitals is the completeness of medical records. The ability to properly maintain medical records facilitates healthcare providers in conducting patient treatments and interventions, while also serving as a valuable information source for hospital management in evaluating and developing healthcare services. However, common issues in medical record documentation include incomplete entries and physicians' insufficient specificity in documenting diagnoses. The aim of this study is to describe the medical records of inpatients at RS X Kabupaten Klaten. This research analyzes the completeness of medical record files at RS X Kabupaten Klaten. A quantitative study was conducted on 98 medical record files by reviewing four components. The results show varying levels of completeness, with some components reaching 100% (such as demographic data), while the lowest was 25.5% (ICD9CM procedures). Critical components like Diet (25.5%) indicate areas in need of improvement. The readability of medical records reached 94.9%. This study identifies areas that require enhancement and suggests strategies such as staff training, routine audits, standardized formats, and the implementation of electronic medical records. Improving the completeness of medical records is expected to enhance patient care quality and hospital operational efficiency.